Ultimate avengers 2 - Johnson, Greg,|d1953-; Kyle, Craig; Michelmore, Guy; Millar, Mark; Hitch, Bryan (Lions Gate Home Entertainment; distributed in the Philippines by Viva Video, 2006)
To save humanity, the Earth's mightiest heroes must reunite for a rematch of heroic proportions.